Cooperation of European Union (EU) and The North Atlantic Treaty Organization (NATO) in Overcoming Terrorism in Europe on 2019-2021 - Gratia Emmanuel Methusala; Christian H.J de Fretes; Suryo Sakti Hadiwijoyo (Journal of Social Science, 2022)
The shift and expansion of security coverage in international relations makes security divided into two types, namely traditional and non-traditional security. Terrorism is a form of non-traditional threat which is still a priority for countries and international organizations around the world. The anxiety that comes from terrorism attacks makes countries and international organizations to form joint policies and cooperation in the context of countering terrorism. The European Union, as a regional organization of countries in Europe contributes to protecting European citizens by acting as the main forum for cooperating and coordinating with member states. Another effort made by the European Union to improve security in their region is to deepen and expand their security cooperation with NATO to eradicate, thwart and eradicate terrorist acts which have continued to increase since 2014. Through the Joint Declaration in 2018, the European Union and NATO deepen the scope of their security cooperation in combating terrorism in Europe.